1975
DOI: 10.1021/jf60202a015
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acids and osmoregulation in penaeid shrimp

Abstract: Shrimp, Penaeus stylirostris Stimpson, were tris and P. aztecus. Regression equations (mmol subjected to increasing and decreasing salinity, 100 g-l) for glycine, glycine plus proline, proline, ranging from 10 to 5 0 %~ Glycine, proline, and alaand total amino acids were 10.156 + 0.1512, 11.426 nine levels increased significantly with increasing + 0.2332, 2.016 + 0.0652, and 21.097 + 0.2492 (desalinity. Only glycine and proline levels decreased creasing salinity), respectively. The regression significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 3 publications
3
15
0
Order By: Relevance
“…Crustacean muscle contains high concentrations of free amino acids, particularly glycine, proline, arginine, glutamate and alanine 19–22 . In the study, higher concentrations of these amino acids were found in the muscle extracts of samples reared in sea water versus those cultured in low salinity water.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Crustacean muscle contains high concentrations of free amino acids, particularly glycine, proline, arginine, glutamate and alanine 19–22 . In the study, higher concentrations of these amino acids were found in the muscle extracts of samples reared in sea water versus those cultured in low salinity water.…”
Section: Discussionmentioning
confidence: 63%
“…Crustacean muscle contains high concentrations of free amino acids, particularly glycine, proline, arginine, glutamate and alanine. [19][20][21][22] In the study, higher concentrations of these amino acids were found in the muscle extracts of samples reared in sea water versus those cultured in low salinity water. The effect of environmental salinity on the free amino acid composition and concentration in penaeid shrimp has also been examined.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the amino acid composition and concentration in the muscle of prawns may affect the quality of the prawn (Wang et al 2004). Crustacean muscles contain high concentration of free amino acids, such as arginine, glycine, proline, glutamine and alanine (Cobb et al 1975). The free amino acids have been shown to function in osmoregulation (Fang et al 1992) and also have a major contribution to the flavor of sea foods (Thompson et al 1980).…”
Section: Amino Acid Profilementioning
confidence: 99%
“…The content of Gly, Arg, Ala and Pro in the muscles of Macrobrachium olfersii under long‐term salinity stress was higher (Mcnamara, Rosa José, Greene, & Augusto, 2004). When the salinity of Penaeus was 10–50‰, Ala, Pro and Gly increased with increased external salinity, and Gly was the main osmotic pressure regulator (Cobb, Conte, & Edwards, 1975). Ala, Pro, Thr, Gly and Arg are the main contributors to osmotic regulation in Penaeus japonicus in low or high salt environments (Via, 1986).…”
Section: Discussionmentioning
confidence: 99%